2022
DOI: 10.1099/ijsem.0.005334
|View full text |Cite
|
Sign up to set email alerts
|

Luteimonas saliphila sp. nov. and Luteimonas salinisoli sp. nov., two novel strains isolated from saline soils

Abstract: Two Gram-stain-negative, motile with single polar flagellum, rod-shaped bacterial strains, named SJ-9T and SJ-92T, were isolated from saline soils from Inner Mongolia, PR China. SJ-9T and SJ-92T grew at pH 6.5–10.0 and 7.0–11.0, 10–35 °C, and in the presence of 0–5 % and 0–8 % NaCl, respectively. Both strains were positive for oxidase, and negative for catalase. The results of phylogenetic analysis based on 16S rRNA gene sequences indicated that SJ-9T clustered with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Saline-alkaline soils cover a wide area of the planet and harbour considerable bacterial diversity with many new species described recently [6,[9][10][11][12][13][14][15]. During a survey of the cultivated bacterial diversity in saline soil in northern China, two strains with high 16S rRNA gene similarities to Ruania strains were isolated from saline soil.…”
Section: Introductionmentioning
confidence: 99%
“…Saline-alkaline soils cover a wide area of the planet and harbour considerable bacterial diversity with many new species described recently [6,[9][10][11][12][13][14][15]. During a survey of the cultivated bacterial diversity in saline soil in northern China, two strains with high 16S rRNA gene similarities to Ruania strains were isolated from saline soil.…”
Section: Introductionmentioning
confidence: 99%
“…gen. n. kalidii of the plant Kalidium cuspidatum). *Data for reference strains were compiled from the literature [5,7,14,58,59]. †These data were calculated from the whole genome sequence.…”
Section: Description Of Luteimonas Kalidii Sp Novmentioning
confidence: 99%
“…viscosa' CGMCC 1.12158 T ; 6, L. wenzhouensis YD-1 T ; 7, L. marina KCTC 12327 T ; 8, L. composti DSM 19790 T ; 9, L. salinisoli SJ-92 T . Data were from this study and our previous research [7] except where indicated otherwise. All the strains are positive for arginine dihydrolase, hydrolysis of aesculin and assimilaton of maltose, fructose and esterase lipase (C8), and negative for glucose fermentation, sunflower acid, citric acid, phenylacetic acid and β-fucosidase.…”
Section: Description Of Luteimonas Endophytica Sp Novmentioning
confidence: 99%
See 1 more Smart Citation